The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/jgh.14853
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden of Crigler–Najjar syndrome: Systematic review and future perspectives

Abstract: Background and Aim Crigler–Najjar syndrome (CNS) results from biallelic mutations of UGT1A1 causing partial or total loss of uridine 5′‐diphosphate glucuronyltransferase activity leading to unconjugated hyperbilirubinemia and its attendant risk for irreversible neurological injury (kernicterus). CNS is exceedingly rare and has been only partially characterized through relatively small studies, each comprising between two and 57 patients. Methods A systematic literature review was conducted to consolidate data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 58 publications
(288 reference statements)
0
39
0
11
Order By: Relevance
“…In the past, bilirubin has been negatively viewed as a toxic bile substance and a biomarker for liver dysfunction. This was mostly reflected from the severe hyperbilirubinemia observed in the extremely rare Crigler–Najjar syndrome with levels in the 400–700 μM range, which can cause brain damage in infants [ 44 ]. The past two decades of heme oxygenase and bilirubin research has shown that bilirubin has many health benefits [ 1 , 2 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, bilirubin has been negatively viewed as a toxic bile substance and a biomarker for liver dysfunction. This was mostly reflected from the severe hyperbilirubinemia observed in the extremely rare Crigler–Najjar syndrome with levels in the 400–700 μM range, which can cause brain damage in infants [ 44 ]. The past two decades of heme oxygenase and bilirubin research has shown that bilirubin has many health benefits [ 1 , 2 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Crigler-Najjar syndrome (CNS) is an AR disorder caused by a defect in the UGT1A1 gene, the product of which (uridine diphosphate glucuronyl transferase) is responsible for the conjugation of bilirubin before its excretion. With an estimated incidence of one per 750000-1000000 live births, CNS is considered an “ultra-rare orphan disease”[ 71 ]. Type 1 is characterized by a complete absence of the enzyme whereas type 2 has 10% of the functioning enzyme[ 71 ].…”
Section: Group Bmentioning
confidence: 99%
“…With an estimated incidence of one per 750000-1000000 live births, CNS is considered an “ultra-rare orphan disease”[ 71 ]. Type 1 is characterized by a complete absence of the enzyme whereas type 2 has 10% of the functioning enzyme[ 71 ]. In type 1 CNS, the exceptionally high unconjugated bilirubin leads to irreversible brain injury in the basal ganglia, hippocampus, subthalamic nuclei and cranial nerves (kernicterus)[ 71 ].…”
Section: Group Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Среди лабораторных показателей зарегистрировано лишь повышение уровня неконъюгированного билирубина, который достигал 270 мкмоль/л (медиана -170 мкмоль/л). При молекулярно-генетическом исследовании UGT1А1 выявлены мутации в 4 Случай из практики у части пациентов наблюдается промежуточная концентрация НБ [8]. При этом весьма сложно по клинической картине провести четкое разграничение между данными патологическими состояниями.…”
unclassified